Fiscal Multipliers During Pandemics - Kinda, Tidiane (IMF Working Papers; Working Paper ;, 2022)
Many countries have deployed substantial fiscal packages to cushion the economic fallout from the COVID-19 pandemic. A historical look at past pandemics and epidemics highlights concomitant public sector support in response to health crises. This paper assesses how fiscal multipliers could vary during health crises, particularly how factors such as social distancing and uncertainty could lower contemporaneous (T) multipliers and increase near-term (T+1 and T+2) multipliers as economies re-open, including due to pent-up demand. Based on Jorda's (2005) local projection methodology, the paper shows that cumulative fiscal multipliers one year after a health crisis is about twice larger than during normal times, particularly in advanced economies. These results suggest that large-scale fiscal support deployed at the onset of the COVID-19 pandemic could have larger than usual lingering impacts on economic activity, which need to be accounted for when calibrating policies.